Vasculitis in Systemic Sclerosis. (2nd August 2010) - Kao, Lily; Weyand, Cornelia
Abstract : Systemic sclerosis (SSc) is a multiorgan connective tissue disease characterized by autoantibody production and fibroproliferative stenosis of the microvasculature. The vascoluopathy associated with SSc is considered to be noninflammatory, yet frank vasculitis can complicate SSc, posing diagnostic and therapeutic challenges. Here, we have reviewed the literature for reports of small-, medium-, and large-vessel vasculitis occurring in SSc. Amongst 88 reported cases of vasculitis in SSc, patients with ANCA-associated vasculitis appear to present a unique subclass in that they combined typical features of SSc with the renal manifestation of ANCA-associated glomerulonephritis. Other vasculitic syndromes, including large-vessel vasculitis, Behcet's disease, cryoglobulinemia, and polyarteritis nodosa, are rarely encountered in SSc patients. ANCA-associated vasculitis needs to be considered as a differential diagnosis in SSc patients presenting with renal insufficiency, as renal manifestations may result from distinct disease processes and require appropriate diagnostic testing and treatment.